ANALYSIS OF VALUE FOR MONEY INCOME BUDGETS GOVERNMENT OF THE CITY OF MEDAN - Hendra Hermain; Aqwa Naser Daulay; Debby Tamara Enre (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
Problems that often arise in the implementation of the Revenue Budget and Regional Expenditure is a waste of budget use done and not on target which should be felt by the community general. This study aims to determine the financial performance of the City Government The terrain is measured using the Value for Money method which consists of economical, efficiency, and effectiveness, and to find out whether financial performance calculated using the Value for Money method in accordance with the Ministry of Home Affairs No. 600,900-327 of 1996. This research was conducted at the Financial Management Agency and Regional Assets of Medan City. This research approach is in the form of an approach descriptive research that is conducted by collecting and presenting data received from the Medan City Government in the form of data on the amount of the Budget Regional Government Revenue and Expenditures Medan City Government thus provides the writerss to analyze and compare with existing theory. The data analysis technique used is descriptive analysis technique qualitative. The results showed that, the performance of Local Government Medan City regency during 2014-2018 has not been economical because it has an average economic ratio of 79% and included in the category of less economical. In terms of efficiency it is less efficient because it has an average efficiency ratio 99.71%. And in terms of effectiveness, the average effectiveness ratio is 82.49% which is in the quite effective category. The economic ratio of the Medan City Government has decreased, the ratio of regional spending efficiency has increased, the ratio the effectiveness of regional income has decreased, and the performance of the City Government The terrain measured using Value for Money has decreased. This happens due to the lack of maximum regional income, as evidenced by regional income that is not able to reach the target, and increased spending Regional Government of Medan City. Then it can be said that the Value for Money Ratio the Medan City Government has not met the standards based on the Minister of Home Affairs. No. 600,900-327 of 1996. Factors causing Value for Money have not been fulfilled standard because of the amount of realization of regional expenditure incurred, and also local governments are not able to achieve the revenue targets that have been determined by the Regional Government